2016
DOI: 10.4081/jlimnol.2016.1198
|View full text |Cite
|
Sign up to set email alerts
|

Co-selection of antibiotic and heavy metal resistance in freshwater bacteria

Abstract: Antibiotic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(59 citation statements)
references
References 72 publications
2
54
0
3
Order By: Relevance
“…The mechanisms employed by bacteria to protect against Zn include reducing absorption, increasing efficiency of efflux, transformation of toxic forms to low toxicity and internal isolation, some of which might cause resistance to antibiotics. There is compelling support for the notion that exposure to heavy metals can act as an indirect selective pressure for maintaining antibiotic resistance (Cesare, Eckert, & Corno, ; Hu, Wang, Li, Li, et al., ; Medardus et al., ). The co‐selection of heavy metal and ARGs in various ecological conditions, such as waters, sediments and soils, which increase the complexity of the ecological role of ARGs, and debases the effectiveness of prevention and control actions, has also been postulated to be an important element for the spread and persistence of ARGs (Hu, Wang, Li, Li, et al., ; Hu, Wang, Li, Shi, et al., ; Peltier et al., ; Seiler & Berendonk, ).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms employed by bacteria to protect against Zn include reducing absorption, increasing efficiency of efflux, transformation of toxic forms to low toxicity and internal isolation, some of which might cause resistance to antibiotics. There is compelling support for the notion that exposure to heavy metals can act as an indirect selective pressure for maintaining antibiotic resistance (Cesare, Eckert, & Corno, ; Hu, Wang, Li, Li, et al., ; Medardus et al., ). The co‐selection of heavy metal and ARGs in various ecological conditions, such as waters, sediments and soils, which increase the complexity of the ecological role of ARGs, and debases the effectiveness of prevention and control actions, has also been postulated to be an important element for the spread and persistence of ARGs (Hu, Wang, Li, Li, et al., ; Hu, Wang, Li, Shi, et al., ; Peltier et al., ; Seiler & Berendonk, ).…”
Section: Discussionmentioning
confidence: 99%
“…Selection for a particular plasmid or mobile element can then be mediated by selection for any one of the resistance determinants it encodes, while the remaining genes are coselected by simple linkage. This has been demonstrated for pollution with disinfectants, and it has been commonly reported that exposure to metals coselects for antibiotic resistance and vice versa . The selective agents do not have to be present at inhibitory concentrations for the effect to be observed .…”
Section: Coselection and Emergent Propertiesmentioning
confidence: 92%
“…This generates opportunities for coselection and fixation of chemical (toxic metals) and resistance determinants in species, and within individual DNA molecules (Johnson et al., ; Zhou et al., ). An investigation by Di Cesare, Eckert, and Corno (), Di Cesare, Eckert, D'Urso et al. () on three WWTPs revealed that heavy metal resistance genes may play a crucial role in the spreading of ARGs via mobile genetic elements.…”
Section: Tracking the Movement Of Resistance Genes In Earth's Criticamentioning
confidence: 99%